Numenius interpreter of the Timaeus. Notes on the exegesis of the verb blépo (frr. 11, 12, 18 des Places) - Volpe, Enrico (Revista Archai, 2022)
Numenius belongs to the contest of the Middle Platonic interpreters of Plato’s dialogues. In Middle Platonism, in fact, spread a tendency to interpret Plato’s philosophy in a systematic way. The most relevant dialogue for this exegetical operation in Middle Platonism was certainly the Timaeus. In this paper I intend to focus on Numenius’ interpretation of pages 28a-29a of Timaeus and examine the exegesis in the light of his onto-theological perspective. In the Timaeus, the use of the verb blépo serves to describe the fact that the demiurge is contemplative of the intelligible paradigm. In Numenius, on the other hand, the association of the verb blépo with the demiurge is intended to show the role of mediator that the second god plays between the first principle and matter. In this way we will show how the passages of the Timaeus are interpreted by Numenius in the light of his dualist metaphysics.